1999
DOI: 10.1055/s-2007-978758
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Human Recombinant Tissue Transglutaminase Measured by Radioligand Assay: Evidence for High Diagnostic Sensitivity for Celiac Disease

Abstract: Celiac disease is associated with endomysial antibodies (EmA), which have recently been reported to be directed to tissue transglutaminase (tTG). To demonstrate binding of antibodies to recombinant tTG, human tTG was cloned, expressed by in vitro transcription/translation and used to develop novel radioligand assays for combined and single detection of immunoglobulin A (IgA) and G (IgG)-specific antibodies. IgA and IgG-tTGA were found in 43 (95.6%) of 45 patients with newly-diagnosed celiac disease verified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 11 publications
(13 reference statements)
5
46
1
Order By: Relevance
“…The presently used IgG anti-tTG ELISA exhibited a high sensitivity (91%) and specificity (96%), whereas other recent studies have reported a sensitivity between 21% and 98% (19,21,32). Detection of IgG anti-tTG antibodies may thus be useful for the diagnosis of celiac disease in patients with selective IgA deficiency (33); this issue needs to be further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…The presently used IgG anti-tTG ELISA exhibited a high sensitivity (91%) and specificity (96%), whereas other recent studies have reported a sensitivity between 21% and 98% (19,21,32). Detection of IgG anti-tTG antibodies may thus be useful for the diagnosis of celiac disease in patients with selective IgA deficiency (33); this issue needs to be further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…The second consideration was that among the several immunoassays developed to detect antitTG-Abs in CD, evidence indicated that those working in fluid-phase were the most specific and sensitive. This was probably a result of the presence of conformational domains in the tTG protein 37,38 that seem to be better preserved in fluidphase rather than in solid-phase procedures. 27 Previously, several attempts were made to detect salivary CD-specific antibodies, in particular AGA and EMA.…”
Section: Discussionmentioning
confidence: 99%
“…17). Gliadin antibodies, both IgA and IgG, have been used in screening and have a sensitivity and specificity for prediction of celiac disease of 70-100%, but most of the relevant studies have been cross-sectional, testing established cases and controls; thus, these estimates are not true estimates of prediction but of identification (16,18,19). Serum reticulin antibodies, notably IgA antibodies against R1-type reticulin, have a sensitivity and specificity at diagnosis in excess of 90% (20).…”
Section: Celiac Diseasementioning
confidence: 99%